2018
DOI: 10.1080/20013078.2018.1541708
|View full text |Cite
|
Sign up to set email alerts
|

More than just exosomes: distinct Leishmania infantum extracellular products potentiate the establishment of infection

Abstract: The use of secretion pathways for effector molecule delivery by microorganisms is a trademark of pathogenesis. Leishmania extracellular vesicles (EVs) were shown to have significant immunomodulatory potential. Still, they will act in conjunction with other released parasite-derived products that might modify the EVs effects. Notwithstanding, the immunomodulatory properties of these non-vesicular components and their influence in the infectious process remains unknown. To address this, we explored both in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…Recently, EVs from L. infantum induced IL-10 and reduced the production of IL-18, suggesting their role in creating a permissive environment for parasite establishment (Castelli et al, 2019 ). Also, injection of L. infantum EVs increased the pro-inflammatory burden resulting in higher parasite loads (Pérez-Cabezas et al, 2018 ). Under our experimental conditions, EVs from L. infantum were also able to induce IL-10 confirming previous findings (Castelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EVs from L. infantum induced IL-10 and reduced the production of IL-18, suggesting their role in creating a permissive environment for parasite establishment (Castelli et al, 2019 ). Also, injection of L. infantum EVs increased the pro-inflammatory burden resulting in higher parasite loads (Pérez-Cabezas et al, 2018 ). Under our experimental conditions, EVs from L. infantum were also able to induce IL-10 confirming previous findings (Castelli et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well reported that Leishmania spp. release exosomes, extracellular vesicles, into their environment (Marshall et al, 2018;Pérez-Cabezas et al, 2019), which would be free to interact with host cells, either through surface binding, fusion with the plasma membrane, or by endocytosis. These vesicles may deliver effector cargos to the target cells interfering with their signaling pathways, priming them for infection (Silverman and Reiner, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The cycle was depicted according to Boitz et al [58]. Leishmania-secreted molecules and exosomes are particularly relevant for infection establishment because parasites and exosomes are co-egested during the insect blood meal [60]. A detailed analysis of the L. infantum secreted proteins (exoproteome) was carried out by Santarem et al [35].…”
Section: Components Of the Proteostasis Networkmentioning
confidence: 99%